IVAN IVANOVICH TUMANOV: A FAMOUS SPECIALIST IN THE PHYSIOLOGY OF ABIOTIC PLANT RESISTANCE - I. A. Kosareva (Труды по прикладной ботанике, генетике и селекции)
In 2014, the scientific community celebrated 120 years since the birth of a well-known expert in plant resistance physiology I. I. Tumanov. The publication contains biographical information and main scientific achievements of I. I. Tumanov. His role in the development of researching plant collections for abiotic resistance is discussed.